Pengembangan Bahan Ajar Berbasis Majalah Dengan Pendekatan Model Problem Based Learning Untuk Meningkatkan Berpikir Kritis Siswa Kelas V DI MI Roudlotus Shibyan Beton Menganti Gresik - Windah Dwi Komaroh; Rahmat Rudianto; Nuru Agustin (InsightEd, 2025)
This study aims to develop magazine-based teaching materials using the Problem Based Learning (PBL) approach to enhance critical thinking skills among fifth-grade students at MI Roudlotus Shibyan Beton Menganti Gresik. The background of the research stems from the lack of engaging and contextual teaching media and students' low critical thinking skills due to monotonous learning materials. This research adopts the ADDIE development model, which includes five stages: analysis, design, development, implementation, and evaluation. Data collection instruments include observation, interviews, questionnaires, and pretest–posttest assessments. Validation results showed that the teaching material was categorized as reasonably feasible to highly feasible, with average validator scores of 60% and 91%. Implementation results revealed positive student responses, with a practicality score of 83.5% and an increase in critical thinking from an average score of 35.75 to 84.25. These findings are supported by theories and prior studies emphasizing the effectiveness of PBL in fostering critical thinking skills. In conclusion, the magazine-based teaching materials integrated with the PBL approach are effective in enhancing student engagement and critical thinking in IPAS subjects.